Attainment of Indian Medical Graduate (IMG) roles through the curriculum: The untold stakeholder perspective - T S Gugapriya; Sithikantha Banarjee; Meenakshi Girish; Sachin Damke; Shital Bhattad (Wolters Kluwer Medknow Publications, 2022)
Background: Graduate Medical Education Regulations 1997 and "Vision 2015" documents were the steps toward training a skilled and competent Indian Medical Graduate (IMG). To implement the changes in the curriculum and to achieve the IMG goal, a nation-wide faculty development program was started by the Medical Council of India in 2009. Even before the introduction of Competency-Based Medical Education (CBME) in 2019, the Indian medical curriculum imbibed and trained the Graduates in competencies relevant for an IMG. This research was to attempt to understand the stakeholder perspective of the contribution of the curriculum in attaining the IMG roles prior to 2019. Methodology: The present multicentric study was carried out among 450 interns belonging to batch 2018 in the state of Maharashtra. A self-administrated, online, structured questionnaire containing 27 items based on IMG roles was used as the study instrument. Descriptive analysis was performed to arrive at the perception of stakeholders. Results: Analysis of self-rating of the competency for IMG roles showed a 30.7% for the "leader and as a team member role". A detailed analysis noted that the majority of the participants lacked confidence in the role of the "medical expert." Competency in the psychomotor domain gained maximum self-rating in comparison to the affective domain. The overall rating about their undergraduate training toward five IMG roles had an unsatisfactory score of 56.3% for the "lifelong learner" role. Conclusion: The study highlighted the stakeholder perspective about curriculum equipping them in developing "leader and a team member" while failing with "lifelong learner" IMG role. The study also emphasized that the attitudinal domain needs addressing by the CBME curriculum.